2010
DOI: 10.1186/1550-2783-7-39
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute and prolonged CRAM supplementation on reaction time and subjective measures of focus and alertness in healthy college students

Abstract: BackgroundThe purpose of this study was to examine the effect of acute and prolonged (4-weeks) ingestion of a supplement designed to improve reaction time and subjective measures of alertness, energy, fatigue, and focus compared to placebo.MethodsNineteen physically-active subjects (17 men and 2 women) were randomly assigned to a group that either consumed a supplement (21.1 ± 0.6 years; body mass: 80.6 ± 9.4 kg) or placebo (21.3 ± 0.8 years; body mass: 83.4 ± 18.5 kg). During the initial testing session (T1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
0
32
0
6
Order By: Relevance
“…Después de la selección y revisión de los artículos, posterior a la eliminación de duplicados, 3 estudios fueron incluidos en el análisis [27][28][29]…”
Section: Resultsunclassified
“…Después de la selección y revisión de los artículos, posterior a la eliminación de duplicados, 3 estudios fueron incluidos en el análisis [27][28][29]…”
Section: Resultsunclassified
“…A study by Hoffman et al (12) involved the use of an S-PS containing supplement using an acute protocol (trial 1) containing 50 mg of PS before testing reaction time, anaerobic power, subjective measures of alertness, energy, fatigue, and focus on 17 male and 2 female college students. After the acute ingestion (trial 1) of the supplement, the subjects either consumed a placebo or the PS containing supplement for 4 weeks and repeated the same testing protocol (trial 2).…”
Section: Pre-exercise Phosphatidylserinementioning
confidence: 99%
“…However, the authors are unable to conclude the magnitude of S-PS (50 mg) on the effects of the subjects because each serving of the supplement also contains: a-glycerophosphocholine (150 mg), choline bitartrate (125 mg), niacin (vitamin B3; 30 mg), pyridoxine HCL (vitamin B6; 30 mg), methylcobalamin (vitamin B12; 0.06 mg), folic acid (4 mg), L-tyrosine (500 mg), anhydrous caffeine (60 mg), acetyl-L-carnitine (500 mg), and naringin (20 mg). The researchers (12) suggest that it is possible that some habituation occurred during the chronic supplementation, which would explain the lack of its effect on trial 2.…”
Section: Pre-exercise Phosphatidylserinementioning
confidence: 99%
“…However, the research performed on athletes has shown that the free choline concentration decrease during intense exercise and that the supplementation of choline can improve endurance, 20,21 and, therefore, choline may be found as an ingredient of many pre-workout sport supplements. 22,23 In these products, choline is mainly found in the form of a cholinium tartrate and less frequently as cholinium citrate. It is known that most of the tartrate is destroyed in the intestinal tract by the present microorganisms, 24 while for the citrate is not found any positive effect on athletic performance or body composition.…”
Section: Introductionmentioning
confidence: 99%